RECONCILING OWNERSHIP RISK UNDER ISLAMIC ECONOMIC LAW: COMPARATIVE ANALYSIS OF INDONESIAN AND MALAYSIAN CONTRACTS - Istianah Zainal Asyiqin; M. Fabian Akbar; Dimas Putra Wirayudha; Ayesha Abul Hisyam (Indonesia Private Law Review, 2025)
Ownership risk (daman milkiyyah) is a core doctrine in Islamic contract law, as it determines the lawful transfer of liability and entitlement to profit in financial transactions, and its misallocation may result in products that are formally Sharia compliant but substantively deficient. This study aims to (1) clarify the juristic foundations of daman milkiyyah and (2) assess its implementation in contemporary Islamic banking products in Indonesia and Malaysia. Using a normative and comparative legal methodology, the research examines statutory and regulatory frameworks, Sharia rulings and fatwas, including those of DSN MUI and Malaysian Sharia governance bodies, classical and contemporary fiqh literature, documented banking practices, and maqasid al sharia as an evaluative lens. The findings reveal differences in regulatory architecture and product implementation between the two jurisdictions, which affect the consistency of ownership risk allocation across instruments such as murabaha, ijara, and asset based financing. These divergences indicate areas where governance standards and operational practices can be strengthened, and the study concludes that clearer ownership risk criteria aligned with maqasid al sharia are necessary to enhance transparency, ensure equitable risk distribution, and support the integrity and resilience of Islamic finance.